2018
DOI: 10.1002/adma.201803498
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a Record‐High Yield Rate of 120.9 for N2 Electrochemical Reduction over Ru Single‐Atom Catalysts

Abstract: The electrochemical reduction of N into NH production under ambient conditions represents an attractive prospect for the fixation of N . However, this process suffers from low yield rate of NH over reported electrocatalysts. In this work, a record-high activity for N electrochemical reduction over Ru single atoms distributed on nitrogen-doped carbon (Ru SAs/N-C) is reported. At -0.2 V versus reversible hydrogen electrode, Ru SAs/N-C achieves a Faradaic efficiency of 29.6% for NH production with partial current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
658
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 810 publications
(701 citation statements)
references
References 36 publications
(63 reference statements)
11
658
2
2
Order By: Relevance
“…Figure 2b shows the XPS spectra of the C 1s for Ru SAs/g-C 3 N 4 and pure g-C 3 N 4 , and only one strong peak appeared at 287.4 eV in pure g-C 3 N 4 , which can be assigned to the sp 2 -hybridized carbon in NCN. [9] These results confirm the absence of crystalline Ru in Ru SAs/g-C 3 N 4 , and that Ru atoms in Ru SAs/g-C 3 N 4 are atomically dispersed. [22] In addition, for Ru SAs/g-C 3 N 4 , a doublet at 280.9 and 285.1 eV was identified, which agreed well with the 3d 5/2 and 3d 3/2 electrons of Ru ions in Ru-N moieties, indicating that Ru ions were successfully incorporated into the g-C 3 N 4 matrix via Ru-N coordination bonds.…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2b shows the XPS spectra of the C 1s for Ru SAs/g-C 3 N 4 and pure g-C 3 N 4 , and only one strong peak appeared at 287.4 eV in pure g-C 3 N 4 , which can be assigned to the sp 2 -hybridized carbon in NCN. [9] These results confirm the absence of crystalline Ru in Ru SAs/g-C 3 N 4 , and that Ru atoms in Ru SAs/g-C 3 N 4 are atomically dispersed. [22] In addition, for Ru SAs/g-C 3 N 4 , a doublet at 280.9 and 285.1 eV was identified, which agreed well with the 3d 5/2 and 3d 3/2 electrons of Ru ions in Ru-N moieties, indicating that Ru ions were successfully incorporated into the g-C 3 N 4 matrix via Ru-N coordination bonds.…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 99%
“…[7] This process takes place under harsh conditions (about 450 °C and 300 bar), is energy intensive, and emits massive amounts of greenhouse gases. [9] Moreover, it has added benefits, such as modularity, scalability, and on-site, on-demand generation, which enables ammonia production in remote areas. In addition, the utilization of aqueous electrolytes has the potential of achieving the simplicity and low cost of this process, because the solvent water can directly serve as the hydrogen source.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Iridium-based and platinumbased electrocatalysts exhibit good performance in OER and hydrogen evolution reaction (HER), respectively,w hile the demerits including scarcity and high cost still limit their largescale practical applications. [15,16] Significantly,i th as also been shown that Ru-based electrocatalysts are active in both HER and OER. [15,16] Significantly,i th as also been shown that Ru-based electrocatalysts are active in both HER and OER.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] From an energy-saving perspective,g reen N 2 to NH 3 fixation methods are strongly desired because the main industrial process for producing NH 3 -the Haber-Bosch process-requires extremely harsh reaction conditions (400-600 8 8C, 20-40 MPa) and causes pollution and greenhouse gas emissions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts.…”
mentioning
confidence: 99%